Profil dan Kompetensi Guru Bahasa Arab Madrasah Aliyah Negeri di Bangka Belitung - Syarifah, Syarifah; Iskandi, Iskandi (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2020)
This article aims to describe the profile of Madrasah Aliyah Negeri Arabic Language Teachers in the Bangka Belitung Islands Province, the relevance of the academic qualifications of Arabic Language Teachers with Subjects taught in Madrasah Aliyah Negeri, and the competence of Arabic Language Teachers in terms of students' perspectives. The research method used is descriptive quantitative, with data collection techniques such as questionnaires and documentation. The results showed that when viewed from academic qualifications, Arabic teachers who already have PBA S1 academic qualifications had a percentage of 80% and other S1 academic qualifications of 20%. Referring to these data, the relevance of Arabic language science to subjects taught based on academic qualifications is 80:20. Whereas if the scientific relevance is reviewed from the professional certificate, Arabic teachers who have professional certificates as professional Arabic teachers are 60% and those that have not been certified are 40%. Based on students' perspectives, the competence of Arabic language teachers in Madrasah Aliyah Negeri Bangka Belitung Islands Province is as follows: Pedagogical Competence with a mean score of 2.64, Professional Competence of 3.00, Social Competence of 3.03, and Personality Competence of 3.04. The overall average score of the four competencies is 2.99 with the interpretation "Enough". Of the three madrasas that are the objects of research, teachers pedagogical competence is a major issue that needs teachers attention.Tujuan dari penelitian ini adalah untuk mendeskripsikan profil guru bahasa Arab Madrasah Aliyah Negeri di Provinsi Kepulauan Bangka Belitung, relevansi kualifikasi akademik guru bahasa Arab dengan mata Pelajaran yang diampu di Madrasah Aliyah Negeri, serta kompetensi guru bahasa Arab ditinjau dari perspektif siswa. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan teknik pengumpulan data berupa angket dan dokumentasi. Hasil penelitian menunjukkan bahwa jika ditinjau dari kualifikasi akademik, guru bahasa Arab yang sudah memiliki kualifikasi akademik S1 PBA memiliki prosentase sebesar 80% dan kualifikasi akademik S1 lainnya sebesar 20%. Mengacu kepada data tersebut relevansi keilmuan guru bahasa Arab dengan mata pelajaran yang diampu berdasarkan kualifikasi akademik sebesar 80:20. Sedangkan jika relevansi keilmuan ditinjau dari sertifikat pendidik, guru bahasa Arab yang memiliki sertifikat pendidik sebagai guru bahasa Arab profesional sebesar 60% dan yang belum tersertifikasi sebesar 40%. Berdasarkan perspektif  siswa kompetensi guru bahasa Arab di Madrasah Aliyah Negeri Provinsi Kepulauan Bangka Belitung adalah sebagai berikut: rerata skor kompetensi pedagogik sebesar 2.64, rerata skor kompetensi profesional sebesar 3.00, kompetensi sosial memiliki rerata skor sebesar 3.03, dan rerata skor untuk kompetensi kepribadian sebesar 3.04. Rerata skor secara umum dari empat kompetensi tersebut adalah 2.99 dengan interpretasi “Cukup”. Dari ketiga madrasah yang menjadi obyek penelitian, kompetensi pedagogik guru menjadi persoalan utama yang perlu mendapat perhatian guru.